Peter's chair - Keats, Ezra Jack. (New York : Harper & Row, 1967)
When Peter discovers his blue furniture is being painted pink for a new baby sister, he rescues the last unpainted item, a chair, and runs away.
Keywords: Picture books; Family relations -- Stories